Mechanical Properties of Dual-Cured Resin Luting Agents for Ceramic Restoration - Keiichi Yoshida, DDS, PhD; Yukiko Tsuo, DDS; Xiangfeng Meng, DDS; and (Journal of Prosthodontics, 2007)
The aim of the present study was to evaluate mechanical properties, including surface hardness, flexural strength, and flexural modulus, of two dual-cured resin luting agents [Clearfil Esthetic Cement (CEC) and Variolink II (VLII)] irradiated through four thicknesses of leucite ceramics (0, 1, 2, and 3 mm) and to evaluate their shear bond strength to zirconia ceramic (Cercon) using each ceramic primer.